Immunophenotypic and molecular features of 'cuplike' acute myeloid leukemias. (February 2014) - Carluccio, Paola; Mestice, Anna; Pastore, Domenico; Delia, Mario; Ricco, Alessandra; Russo‐Rossi, Antonella; Casieri, Paola; Liso, Arcangelo; Martelli, Maria Paola; Albano, Francesco; Specchia, Giorgina
Abstract Nuclear invaginations, also referred to as fishmouth or cuplike nuclei, have long been identified in microgranular APL, myelomonocytic and monocytic AMLs. More recently, this typical morphological feature has been associated with NPM1 and FLT3 mutations, as well as with the lack of CD34 and HLA‐DR expression. In this study, we retrospectively analyzed the morphologic, immunophenotypic, cytogenetic, and molecular features of 68 patients with AML. A cuplike nuclear invagination was detected in more than 10% of blast cells in 15 (22%) cases. Our data show that a cuplike morphology is associated with FLT3‐ITD positivity, as well as with the loss of CD34 and HLA‐DR expression. The results were not significantly modified when a higher cutoff of cuplike cells was used. Our results are not sufficient to suggest that cuplike AML could represent a distinct subtype, but further investigations could yield a better characterization of this feature in patients with AML.